Perception of the Medical Resident in EsSalud Hospitals - Arequipa. - Lily Montesinos Valencia (2020)
Objective: Describe the Perception of the Medical Resident in EsSalud hospitals. Materials and Methods: A descriptive, prospective study was carried out on first-year residents of all specialties at: Carlos Alberto Seguin Escobedo National Hospital and at Yanahuara-Essalud Hospital from October to December 2018. A self-administered survey was used, which Consists of two sections: 1) Formative aspects: general data, information about the courses taught by the university, access to bibliographic information, resident tutoring, clinical training, research training and 2) Comprehensive perception: curriculum evaluation, aspects to improve during residence. Results: female sex predominated among residents with 63.64%. 45.45% of residents were informed about the courses that were taught. 100% had access to the digital library but only 15% consulted it. 87.88% knew their tutor and 57.58% performed academic-clinical activities partially specific to their specialty with their tutor. The research was deficient in the residents of the hospital headquarters. In relation to the curricular evaluation, only 33.33% considered it objective. The aspects to be improved were the increase in external rotations by 78.779% and thesis advice by 57.58%. The general perception of the Medical Resident Program was positive and subjective in 72.72%. The data obtained will allow the development of a Higher Teaching Quality Management Plan.